PENGARUH Benzyl Adenin DAN MEDIA DASAR PADA PERBANYAKAN EMBRIO ANGGREK SECARA In Vitro - Caecilia Puspita C.P.A; Sudiarso Sudiarso; Tatik Wardiyati (BUANA SAINS, 2011)
In Indonesia, orchid is one of advanted crop. Crop multiplication of orchids usually produce with seed culture. Each embryo from seed culture can be multiplied by mericlone. The objective of this research is determine the type of media benzyl adenine concentration for growing and embryo’s proliferation of Phaleaenopsis amabilis. The research used complete randomized design factorial consist of 2 factors with 3 replications. First factor is type of media consist of 3 levels which are ½ Murashige and Skoog (½ MS), Vacin and Went (VW), New Phalaenopsis (NP). Second factor is Benzyl adenine concentration consist of 4 levels which are 0 ppm, 0.5 ppm, 1 ppm and 1.5 ppm. Each bottle are inoculated by 5 embryos/PLB of white Phalaenopsis amabilis. Data had been analyzed with F test in 5% level. The highest number of embryos per explants are shown from combination between ½ MS media with 0.5ppm BA. The results showed that highest number of leaves and roots per explants are from NP media. Media without benzyl adenine produced the highest number of leaves and roots. The highest number of diameter is produced by VW media which combine with 1.5 ppm benzyl adenine